Deletion of SDF-1 or CXCR4 regulates platelet activation linked to glucose metabolism and mitochondrial respiratory reserve. (19th May 2022) - Li, Yi; Feng, Ziqian; Zhu, Luochen; Chen, Ni; Wan, Qin; Wu, Jianbo
Abstract: Stromal cell-derived factor 1 (SDF-1, also known as CXCL12) and its receptor CXCR4 have shown to play a role in the homing and engraftment of hematopoietic stem and progenitor cells. SDF-1 is highly expressed in platelets and involved in thrombosis formation. However, the exact roles of platelet-derived SDF-1 and CXCR4 in platelet activation and mitochondrial function have not been revealed yet. Deletion of Sdf-1 and Cxcr4 specifically in platelets decreased agonist-induced platelet aggregation and dramatically impaired thrombin-induced glucose uptake. In SDF-1-deficient and CXCR4-deficient platelets, intracellular ATP secretions were reduced when activated by the addition of thrombin. SDF-1 deficiency in platelets can impair the routine respiration during resting state and maximal capacity of the electron transfer system (ETS) during activated state. Mitochondrial respiration measurements in permeabilized platelets indicated an impaired function of the oxidative phosphorylation system in -SDF-1 or CXCR4-deficient platelets. These results suggested a novel role of the SDF-1/CXCR4 axis in modulating platelet energy metabolism and activation by regulating mitochondrial respiration, glucose uptake, and ATP production.